Palmar Ulnar Artery Perforator Free Flap for Fingertip Reconstruction: Anatomical and Clinical Study. (9th May 2018) - Pak, Chang Sik; Jeon, Ji-In; Myung, Yujin; Lee, Yung Ki; Kim, Byung Jun; Jeong, Jae Hoon; Kim, Baek-Kyu
Abstract : Background . Fingertips are a common site for hand injuries. The ideal substitute for fingertip pulp is tissue that matches texturally with minimal donor site morbidity. We described anatomical findings from cadaveric studies and the reliability of the palmar ulnar artery perforator (PUAP) free flap techniques for the reconstruction of fingertips injuries. Methods . The cadaveric study involving 8 hands was conducted to illuminate the anatomy of the hypothenar region. We investigated the emerging point of perforators, diameter of the artery at the origin, and the length of the pedicle. Forty-four patients with fingertip injuries underwent fingertip reconstruction using PUAP free flaps. Data on the baseline patient demographics, hospital courses, and flap sizes were obtained retrospectively. The 6-month postoperative sensory capacity was determined using a 2-point discrimination test. Results . The cadaveric study found that the PUAP pedicles arose from the superficial palmar arch, the mean length of pedicles, and the diameter and location of perforators were also analyzed. The PUAP flap sizes varied from 2.0 × 2.3 cm to 2.5 × 3.5 cm, and the mean operative time was 124 min. In all cases, we performed neurorrhaphy for fingertip sensory restoration. All donor sites were closed primarily, and the 2-point discrimination test result was5.7 ± 0.87 mm 6 months after surgery. Conclusions . We confirmed the anatomical consistency of the PUAP. Among the numerous reconstruction options available for fingertip injuries, the PUAP free flap is a useful fingertip reconstruction option.